Study of Analysis of The Implementation of Behavioristic Learning Theory in Arabic Language Learning at Unity Theory with Direct Method for Beginner - Junaedi, Junaedi (Jurnal Edusci, 2024)
This study analyzes the implementation of behavioristic learning theory in learning Arabic. It is an all-in-one method for beginners with direct methods. A literature study was used to collect qualitative data from literature relevant to behavioristic learning theory and direct methods in learning Arabic Unity theory. The study results indicate a strong suitability between Behavioristic theory and learning Arabic Unity theory. Behavioristic theory emphasizes the importance of repetition, reinforcement, and association, which are the core of direct methods in learning Arabic Unity theory. It is hoped that the results of this study can provide valuable contributions in developing learning strategies that can improve students' understanding of Arabic Unity theory.